Rapid reductions in prices for generic sofosbuvir and daclatasvir to treat hepatitis C - Andrew Hill; Bryony Simmons; Dzintars Gotham; Joseph Fortunak (Elsevier, 2016)
Objectives: Novel treatments for hepatitis C demonstrate high cure rates, but current high prices can be a barrier to rapid global treatment scale-up. Generic competition can rapidly lower drug prices. Using data on exports of raw materials in 2015, we calculated currently feasible generic prices of sofosbuvir and daclatasvir. Methods: Data on per-kilogram prices of sofosbuvir and daclatasvir active pharmaceutical ingredients (API) exported from India were extracted from an online database. To the cost of the amount of API needed for a 12-week treatment course, we added cost estimates for formulation (40%), packaging (US$0.35/month), and a mark-up (50%). Results: Between 1 January and 15 October 2015, over 5 tons of sofosbuvir were exported, with prices decreasing by US$702/kg/month, and observed prices of US$2501/kg in early September. Over the same period, 84 kg of daclatasvir were exported, with prices decreasing by US$1664/kg/month to US$1897/kg. Using the price estimation algorithm, we estimated the price of a generic sofosbuvir-daclatasvir combination regimen at US$200 per patient for a 12-week treatment course. Conclusion: The costs of generic production of sofosbuvir and daclatasvir are rapidly decreasing. Sofosbuvir-daclatasvir combination treatment could be produced for US$200 per patient per 12-week course.